(untitled) - Moseley, William G. (Hoboken, NJ, 2014)
A first of its kind and in my opinion, a complete winner. An introductory textbook that presents in an engaging and accessible style, geography's unique approach to environmental issues
Keywords: Human ecology,Human geography,Sinh thái nhân văn,Địa lý nhân văn